7. Effect of Soya Wastes Probiotic and Palm Kernel Addition Fermented by Aspergillus niger to the Cellulase Activity in Broilers Digestive Tract - Nurliana Nurliana; Anna Farida; Sugito Sugito; Al Azhar; Razali Razali; Cut Nila Thasmi (Universitas Syiah Kuala, 2019)
This study aimed to determine the cellulase activity in broilers digestive tract after the treatment of soya wastes and palm kernel fermented by A.niger (AKBIS Prob) in the ration. This study used a complete randomized factorial design, which consists of two factors, namely the AKBIS Prob composition factor and the duration of AKBIS Prob. Twenty four broilers were divided into four groups by randomized and three replications of each. The feed supplement combinations were P0 (commercial), P1 (commercial and AKBIS Prob 2%), P2 (commercial and AKBIS Prob 4%), and P3 (commercial and AKBIS Prob 6%). The intestine preparation was taken at the 22 and 36 days to extraction and detection the cellulase activity concentration. Data were analyzed using variance analysis of factorial patterns. AKBIS Prob 2,4 and 6% was no effect (P 0.05) to the cellulase activity in the small and large intestine, while the treatment duration was significant (P0,05) in the small intestine but neither in the large intestine (P0,05) to the cellulase activity. The addition of AKBIS Prob 2.4 and 6% had no effect (P 0.05) on the concentration of cellulase activity in the small intestine and large intestine, while the duration the treatment was very significant (P 0.05) in the small intestine and neither in the large intestine (P 0.05) on the concentration of cellulase activity. The AKBIS administration in the ration for 22 days can increase the activity and concentration of cellulase activity in the small intestine of the digestive tract of broiler chickens.